Analysis of Partnership Patterns Between Gaharu Plant Farmers and PT. Cahaya Gaharu Langkat - Marpaung, Suci Tasya Hasian; Siregar, Gustina; Sinaga, Hardiansyah (ITScience (Information Technology and Science), 2024)
This research aims to determine the partnership pattern between gaharu plant farmers and PT. Cahaya Gaharu Langkat and to determine the effectiveness of the partnership program. The type of research used is descriptive and qualitative. Determining the research location was carried out deliberately, namely selecting subjects based on certain characteristics or characteristics that were previously known. The data collected consisted of primary data, namely direct interviews with respondents, and secondary data from relevant agencies related to this research. The results of this research are 1). The partnership pattern that occurs between PT. Cahaya Gaharu Langkat with gaharu plant farmers is a partnership pattern for Agribusiness Operational Cooperation. The development of gaharu plant farmers land is fully managed by farmers with the assistance of the company. 2). The level of effectiveness of the partnership pattern between gaharu plant farmers and PT. Cahaya Gaharu Langkat is 79.25 which is in the effective category. With the program target accuracy indicator, the score was 91%, the program socialization indicator was 78%, the program objective was 67%, the program monitoring indicator was 81%.